Cannabinoid Receptor Type 1 Expression in the Developing Avian Retina: Morphological and Functional Correlation With the Dopaminergic System - da Silva Sampaio, Luzia; Kubrusly, Regina C. C.; Colli, Yolanda P.; Trindade, Priscila P.; Ribeiro-Resende, Victor T.; Einicker-Lamas, Marcelo; Paes-de-Carvalho, Roberto; Gardino, Patricia F.; de Mello, Fernando G.; De Melo Reis, Ricardo A. (Frontiers in Cellular Neuroscience, 2018)
The avian retina has been used as a model to study signaling by different neuro- and gliotransmitters. It is unclear how dopaminergic and cannabinoid systems are related in the retina. Here we studied the expression of type 1 and 2 cannabinoid receptors (CB1 and CB2), as well as monoacylglycerol lipase (MAGL), the enzyme that degrades 2-arachidonoylglycerol (2-AG), during retina development. Our data show that CB1 receptor is highly expressed from embryonic day 5 (E5) until post hatched day 7 (PE7), decreasing its levels throughout development. CB1 is densely found in the ganglion cell layer (GCL) and inner plexiform layer (IPL). CB2 receptor was also found from E5 until PE7 with a decrease in its contents from E9 afterwards. CB2 was mainly present in the lamination of the IPL at PE7. MAGL is expressed in all retinal layers, mainly in the IPL and OPL from E9 to PE7 retina. CB1 and CB2 were found both in neurons and glia cells, but MAGL was only expressed in Müller glia. TH amacrine neurons express CB1 receptor in the INL and GCL cells around E14. Older retinas (PE7) show CB1 positive cells mainly in the INL and co-expression of CB1 and TH are shown in a few cells when both systems are mature. CB1 co-localized with TH and was heavily associated to D1 receptor labeling in primary cell cultures. Finally, cyclic AMP (cAMP) was activated by the selective D1 agonist SKF38393, and inhibited when cultures were treated with WIN55,212-2 (WIN) in a CB1 dependent manner. The results suggest a correlation between the endocannabinoid and dopaminergic systems during the avian retina development. Activation of CB1 limits cAMP accumulation via D1 receptor activation and may influence embryological parameters during avian retina differentiation.